2014
DOI: 10.1038/srep07309
|View full text |Cite
|
Sign up to set email alerts
|

Intervention-induced enhancement in intrinsic brain activity in healthy older adults

Abstract: This study examined the effects of a multimodal intervention on spontaneous brain activity in healthy older adults. Seventeen older adults received a six-week intervention that consisted of cognitive training, Tai Chi exercise, and group counseling, while 17 older adults in a control group attended health knowledge lectures. The intervention group demonstrated enhanced memory and social support compared to the control group. The amplitude of low frequency fluctuations (ALFF) in the middle frontal gyrus, superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 57 publications
2
43
0
1
Order By: Relevance
“…Elevating the public awareness of mental disorders should be prioritized as well as enhancing the medical support resources for early detection, intervention and treatment of mental illness in the elderly. Professional interventions, comprising psychotherapy and combined cognitive-psychological-physical intervention not only can mitigate subclinical depression, but can also delay age-related brain and cognitive deterioration and improve overall mental health (Cuijpers et al, 2014; Li et al, 2014; Yin et al, 2014). A recommendation to medical universities is to train more geriatric care professionals to meet the increasing demand.…”
Section: Health Challenges In the Chinese Elderlymentioning
confidence: 99%
“…Elevating the public awareness of mental disorders should be prioritized as well as enhancing the medical support resources for early detection, intervention and treatment of mental illness in the elderly. Professional interventions, comprising psychotherapy and combined cognitive-psychological-physical intervention not only can mitigate subclinical depression, but can also delay age-related brain and cognitive deterioration and improve overall mental health (Cuijpers et al, 2014; Li et al, 2014; Yin et al, 2014). A recommendation to medical universities is to train more geriatric care professionals to meet the increasing demand.…”
Section: Health Challenges In the Chinese Elderlymentioning
confidence: 99%
“…Resting-state activity has been reported to predict behavioral performance [22]. Therefore, spontaneous neural activity in left IPL and functional connectivity between left IPL and precuneus may be utilized to complement the assessments of moral injury/PTSD and monitoring the response to clinical intervention [55].…”
Section: Alff and Falff Whole-brain Analyses Findingsmentioning
confidence: 99%
“…Yin et al reported that a physical activity-based intervention increased spontaneous resting-state activity in the right MFG [Yin et al, 2014]. Moreover, Voss et al reported an increase in resting-state connectivity resulting from a physical activity-based intervention in the frontal executive network, a collection of brain areas in the frontal cortex [Voss et al, 2010b].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, opercular insular connectivity can be enhanced through active learning [Albert et al, 2009], which may be a result of the ILI. Yin et al speculate that the increased activity and connectivity in the right MFG is associated with increased feeling of subjective well-being resulting from an intervention [Yin et al, 2014]. This assessment is based on the right MFG’s involvement in modulation of depressive states [Wang et al, 2008], as well as their prior study demonstrating the association between the functional connectivity in the right MFG and subjective well-being [Li et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation